A survey of noise and hearing patterns in an industry in Mysore city - Mahananda P (Journal of All India Institute of Speech and Hearing, 1972)
A Survey of Hearing Patterns of Industrial Workers in Mysore City'.The problem is to find out the pattern of hearing among the industrial workerswho work in different noise environment and to find the relation between thesetwo factors.